1994
DOI: 10.1093/beheco/5.3.339
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive fitness and reproductive strategies in dwarf mongooses

Abstract: Dwarf mongooses (Helogale parvula) are small, communally breeding carnivores found in woodland and tree-savanna throughout Africa. Within a pack, socially subordinate mongooses do not normally breed, yet they invariably participate in all aspects of parental care. The primary alternative to tolerating reproductive suppression is dispersal, which shortens the wait for dominance and breeding. Here, we calculate the annual inclusive fitness payoffs to the dispersing and nondispersing strategies for males and fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(72 citation statements)
references
References 0 publications
1
71
0
Order By: Relevance
“…Usually suppression is complete; when subordinates breed, they risk infanticide by dominants (Digby 1994), and probably have little chance of raising o spring successfully even without infanticide. Callitrichid maternal energetics and mating systems ®nd parallels among communally breeding carnivores (e.g., dwarf mongoose: Creel and Waser 1994;reviewed in Creel and Creel 1991). They are unusual for primates, but partial reproductive suppression, coupled with targeted aggression, may be common in RN species (above; cf.…”
Section: Social Alternative: Male Harassmentmentioning
confidence: 99%
“…Usually suppression is complete; when subordinates breed, they risk infanticide by dominants (Digby 1994), and probably have little chance of raising o spring successfully even without infanticide. Callitrichid maternal energetics and mating systems ®nd parallels among communally breeding carnivores (e.g., dwarf mongoose: Creel and Waser 1994;reviewed in Creel and Creel 1991). They are unusual for primates, but partial reproductive suppression, coupled with targeted aggression, may be common in RN species (above; cf.…”
Section: Social Alternative: Male Harassmentmentioning
confidence: 99%
“…This makes those exceptional cases where cooperators are unrelated particularly interesting, because these groups should confer direct benefits, or a probability of direct benefits, on all their members, a condition which should have a great impact on the nature of their cooperation. Unrelated group members have been reported in kingfishers 2 , manakins 3 , mongooses 4 , halictine bees 5 and ant foundresses 6,7 .…”
mentioning
confidence: 99%
“…However, the authors believe that estimates of the survival rate of emigrants and philopatric animals could be calculated from existing census data and behavioral observations to estimate such a parameter. Waser et al (1994) demonstrated the effectiveness of this approach using data from a number of observational studies on dwarf mongooses, Helogale parvula (Rood, 1983(Rood, , 1987(Rood, , 1990Creel and Waser, 1994). This study showed that in this species, older and more experienced individuals had greater dispersal success.…”
Section: Ecological Factorsmentioning
confidence: 90%